The other woman - Roos, Don; Portman, Natalie, 1981-; Kudrow, Lisa; Cohen, Scott, (Scott E.), 1961-; Waldman, Ayelet (Orland Park, IL : MPI Home Video, 2011)
A woman whose marriage began as an extramarital affair tries to forge a bond with her stepson after her infant daughter dies unexpectedly.
Based on the novel "Love and other impossible pursuits" by Ayelet Waldman.
Natalie Portman, Lisa Kudrow, Scott Cohen, Charlie Tahan, Lauren Ambrose.
MPAA rating: R.
DVD, Dolby digital 5.1.
In English with optional Spanish subtitles.
Closed-captioned.
Keywords: Waldman, Ayelet -- Film adaptations; Infants -- Death -- Drama; Stepfamilies -- Drama; Grief -- Drama; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films